The Behaviour of a Modified Box-Cox Regression Model when Some Values of the Dependent Variable are Close to Zero - Magee, Lonnie (The Review of Economics and Statistics, 1988)
Lonnie Magee, The Behaviour of a Modified Box-Cox Regression Model when Some Values of the Dependent Variable are Close to Zero, The Review of Economics and Statistics, Vol. 70, No. 2 (May, 1988), pp. 362-366